Effect of Intravenous Acetaminophen on Mean Arterial Blood Pressure: A Post Hoc Analysis of the EFfect of Intravenous ACetaminophen on PosToperative HypOxemia After Abdominal SurgeRy Trial. (15th November 2021) - Bravo, Mauro; Bakal, Omer; Rivas, Eva; Mascha, Edward J.; Pu, Xuan; Mosteller, Lauretta; Rodriguez-Patarroyo, Fabio; Essber, Hani; AlGharrash, Ahmed; Turan, Alparslan
Abstract : BACKGROUND: Acetaminophen is commonly used as part of multimodal analgesia for acute pain. The intravenous formulation offers a more predictable bioavailability compared to oral and rectal acetaminophen. There have been reports of hypotension with intravenous acetaminophen attributable to centrally mediated and vasodilatory effects. We tested the hypothesis that in adults having abdominal surgery the use of intravenous acetaminophen versus placebo for postoperative pain management is associated with a decrease in mean arterial pressure (MAP) after its administration. METHODS: This is a substudy of eFfect of intravenous ACetaminophen on posToperative hypOxemia after abdominal surgeRy (FACTOR) trial (NCT02156154). FACTOR trial randomly assigned adults undergoing abdominal surgery to either 1 g of acetaminophen or placebo every 6 hours during the first postoperative 48 hours. Continuous monitoring of blood pressure was obtained by noninvasive ViSi Mobile device (Sotera Wireless, Inc, San Diego, CA) at 15-second intervals during initial 48 hours postoperatively. We excluded patients without continuous monitoring data available. The primary outcome was the MAP difference between MAP 5 minutes before study drug administration (baseline) and MAP 30 minutes poststudy drug administration initiation. We used a linear mixed effects model to assess the treatment effect on MAP change. The secondary outcome was MAP area under baseline (AUB) during the 30 minutes after treatment. In a sensitivity analysis of change in MAP from predrug to postdrug administration, we instead used postdrug MAP as the outcome adjusting for the baseline MAP in the model. RESULTS: Among 358 patients analyzed, 182 received acetaminophen and 176 placebo. The mean (standard deviation [SD]) of average MAP change was −0.75 (5.9) mm Hg for the treatment and 0.32 (6.3) mm Hg for the placebo. Acetaminophen was found to decrease the MAP from baseline more than placebo after drug administration. The estimated difference in mean change of MAP was −1.03 (95% confidence interval [CI] −1.60 to −0.47) mm Hg; P < .001. The sensitivity analysis showed postoperative MAP in the acetaminophen group was 1.33 (95% CI, 0.76-1.90) mm Hg lower than in the placebo group ( P < .001). The median of MAP AUB was 33 [Q1 = 3.3, Q3 = 109] mm Hg × minutes for the treatment and 23 [1.6, 79] mm Hg × minutes for the placebo. Acetaminophen was found to increase the AUB with an estimated median difference of 15 (95% CI, 5-25) mm Hg × minutes ( P = .003). CONCLUSIONS: Intravenous acetaminophen decreases MAP after its administration. However, this decrease does not appear to be clinically meaningful. Clinicians should not refrain to use intravenous acetaminophen for acute pain management because of worries of hypotension.